Seasonal dynamics of phytoplankton shapes the annual variation of community in the coastal waters of Qinhuangdao, a high-frequency HAB area in North China - Junlan Huang; Chao Liu; Jiabo Zhang; Gang Wang; Wenjiao Tang; Xiaoyang Yu; Qingchun Zhang; Rencheng Yu (Journal of Oceanology and Limnology, 2026)

Synergy effect of nZVI@LDH assembling anaerobic granular sludge boosts anaerobic digestion for enhanced sulfamethoxazole degradation and methanogenesis - Yanyan Pei; Junlan Chen; Kaiqi Lian; Yi Tang; Xiong Zhuo; Jinfeng Chen; Zhuwu Jiang (Chemical Engineering Journal, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

A novel fenton-like catalyst for efficient degradation of tetracycline: Application of the concept of “treating the wastes with wastes” - Lang Ran; Yajuan Zheng; Xu Zhang; Weidong Xiao; Lingxiao Zhu; Junlan Tang; Yaoguo Wu; Lincheng Zhou (Waste Management, 2025)

Distribution Range and Richness of Plant Species Are Predicted to Increase by 2100 due to a Warmer and Wetter Climate in Northern China - Ying Sun; Yan Deng; Shuran Yao; Yuan Sun; Abraham Allan Degen; Longwei Dong; Jiali Luo; Shubin Xie; Qingqing Hou; Dong Tang; Yuzhen Sun; Junlan Xiong; et al. (Global Change Biology, 2025)
The warming global climate is threatening terrestrial ecosystem stability, including plant community structure and diversity. However, it remains unclear how distribution, richness, and turnover of plant species are impacted by warming and wetting in northern China. In the present study, species distribution models were applied to predict the spatial distribution of 5111 plant species based on 111,071 occurrence records in northern China. Additionally, variations in species richness and turnover rates were predicted for 2100 under 3 scenarios. The results indicated that approximately 70% of plant species will expand in their distribution, resulting in an increase in species richness. These changes will be driven mainly by temperature seasonality (TSN), annual precipitation (MAP), and mean temperature of the coldest quarter (MTCQ). However, about 30%–40% of the species will face extinction risks, including a considerable number of endemic and Red‐Listed species, and suitable habitat loss (LSH) will exceed 30%. Narrow‐ranging species will be more likely to lose a larger percentage of their suitable habitats than wide‐ranging species, highlighting their sensitivity to environmental changes. Importantly, it emerged that species turnover rates will increase linearly with ecological vulnerability at the grid level, indicating that community structure and species composition are easily affected by climate change in ecologically vulnerable areas. Therefore, biodiversity hotspots with high species richness in the southern study areas, as well as regions exhibiting both fast species turnover and significant ecological vulnerability, should be prioritized for conservation. These findings provide insights into how species composition and richness in plant communities vary with global climate change and provide effective ecological conservation and management strategies.

Enhanced methanogenesis and efficient ciprofloxacin degradation via nZVI@LDH in an electricity-driven anaerobic bioreactor: A biotic-abiotic hybrid system for ROS regulation and ARGs mitigation - Jinfeng Chen; Yi Tang; Xinyan Chen; Junlan Chen; Zhang Yan; Xiao Yao; Hongyu Zhang; Yanyan Pei; Zhuwu Jiang (Journal of Hazardous Materials, 2025)

Ternary Fenton-like material (γ-Fe2O3/MoS2/PANI) supported on polysulfate membrane for high-performance catalytic degradation of tetracycline solution - Jiaming Xu; Heng Zhang; Lian-Biao Zhao; Xiaohong Xing; Junlan Tang; Xiangru Zhou; Lincheng Zhou (Journal of Water Process Engineering, 2025)

Material flow analysis and statistical entropy evaluation of plastic packaging for express delivery in China - Yuanyuan Tang; Jiansu Mao; Guangjie Yu; Jiarui Li; Junlan Wang (Environmental Science and Pollution Research, 2024)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)